ANALISIS PENGARUH PENGETAHUAN MEREK TERHADAP MINAT BELI PADA SMARTPHONE SAMSUNG GALAXY SERIES (Studi Pada Mahasiswa Universitas Brawijaya) - Alqadrie, Syarifah Soraya (Jurnal Ilmiah Mahasiswa FEB, 2017)
The objectives of this research are to examine and analyze the simultaneous and/or partial influence of brand knowledge, which consist of brand awareness and brand image,   on   customers’  purchase   intention   toward   Samsung   Galaxy   series smartphone and  to  determine  the  variable  that  has  a  dominant  influence  on purchase intention. This explanatory research explains causal relationship between dependent variable and  independent variables through hypothesis testing. Using purposive sampling technique, 210 Brawijaya University students were selected as the  respondents. To identify the  influence of independent variables on dependent variable, this research  uses multiple linear regression analysis. F test, t test, and dominant  test  were  used  to  test  the  hypothesis.  Based  on the  result  of  data advisability test, namely validity and reliability tests, the indicators of this research are stated valid and reliable the result of classical assumption test indicates that the regression model  in  this  research  is normally distributed and free of multicollinearity,   and   heteroscedasticity.   The   calculation   of   multiple   linear regression analysis in this research can be interpreted that brand awareness and brand image simultaneously and partially have a significant influence on purchase intention.  The  result also  shows that brand image has a  dominant influence on purchase intention.keywords : Brand Knowledge, Brand Awareness, Brand Image, Purchase Intention